GMF as an Actin Network Remodeling Factor. Issue 9 (September 2018) - Goode, Bruce L.; Sweeney, Meredith O.; Eskin, Julian A.
Abstract : Glia maturation factor (GMF) has recently been established as a regulator of the actin cytoskeleton with a unique role in remodeling actin network architecture. Conserved from yeast to mammals, GMF is one of five members of the ADF-H family of actin regulatory proteins, which includes ADF/cofilin, Abp1/Drebrin, Twinfilin, and Coactosin. GMF does not bind actin, but instead binds the Arp2/3 complex with high affinity. Through this association, GMF catalyzes the debranching of actin filament networks and inhibits actin nucleation by Arp2/3 complex. Here, we discuss GMF's emerging role in controlling actin filament spatial organization and dynamics underlying cell motility, endocytosis, and other biological processes. Further, we attempt to reconcile these functions with its earlier characterization as a cell differentiation factor. Highlights: GMF is structurally related to cofilin, and is a conserved regulator of the actin cytoskeleton. GMF triggers actin filament debranching by targeting the Arp2/3 complex at branch sites. GMF also inhibits free Arp2/3 complex from nucleating actin assembly. GMF localizes to the leading edge, and its debranching activity is critical for lamellipodial retraction, a key step in directed cell migration.